Navigating the application of new innovations: Establishing an indocyanine green lymphography clinic in Australia. (28th August 2022) - Trevethan, Megan; Bennett, Sally; Doig, Emmah; Patterson, Freyr; Pigott, Amanda
Abstract: Translation of evidence into practice in healthcare is challenging, particularly with new innovations. Indocyanine Green (ICG) lymphography is a novel innovation where the superficial lymphatics are imaged to provide information about lymphoedema diagnosis and to guide individualised therapy for a person's long‐term chronic management of lymphoedema, supporting care across the continuum to the community setting. Despite the unique information ICG lymphography provides, the technology itself is complex and highly specialised and currently has limited adoption in clinical practice. This paper sought to determine the barriers and enablers to establishing an ICG lymphography clinic within an outpatient lymphoedema service by exploring staff perceptions and experiences. An interpretive descriptive design was used with semi‐structured interviews of key staff participants from a quaternary public hospital six months after ICG lymphography clinic establishment. An interview guide was developed, underpinned by the Consolidated Framework for Implementation Research (CFIR), to guide the inquiry. Interview data were transcribed, inductively coded and analysed to identify themes. All eligible management, clinical and ancillary staff were included ( N = 8). Four key themes were identified from the data as essential to implementation success. These were support is critical for implementation ; beliefs about the technology ; practicalities are achievable ; and sustainability for ongoing success . Themes were found to be interrelated and centred around support from staff and the organisation as a critical process facilitator. The study demonstrated an ICG lymphography clinic can be successfully established as part of an outpatient lymphoedema service. Key enablers related to positive staff attitudes and beliefs about ICG lymphography and its application. Future implementation sites may consider that although the complexity of this innovation creates process challenges, the use of an implementation framework can assist in identifying determinants of success for effective implementation to practice.